Comparative phytoremediation potential and heavy metal accumulation patterns in Amaranthus viridis and Lactuca sativa: Implications for food safety and environmental management in contaminated agroecosystems - Dankaka, A. H.; Shah, M. M.; Umar, A. B. (Recent Research in Science and Technology, 2025)
This study comprehensively evaluated the phytoremediation potential and physiological responses of Amaranthus viridis and Lactuca sativa to heavy metal contamination (Cd, Pb, Hg, and Zn) under controlled screen house conditions at Bayero University, Kano, Nigeria. Using a randomized complete block design with three replicates, plants were grown in both uncontaminated and contaminated sandy soil, with metal concentrations verified weekly via flame atomic absorption spectrometry (FAAS). Growth parameters (leaf number, shoot length, leaf area, fresh/dry weight, and biomass) were measured alongside heavy metal accumulation in roots, stems, and leaves, with bioconcentration (BCF) and translocation factors (TF) calculated to assess uptake and mobility. Results demonstrated A. viridis exhibited superior tolerance to metal stress, maintaining higher growth metrics than L. sativa under contamination (e.g., 8.5 vs. 4.8 leaves under Cd stress). Both species accumulated metals beyond WHO/FAO safety limits, with A. viridis roots showing exceptional Pb retention (35.00 mg/kg) and significant Cd/Hg translocation (TF>1), while L. sativa preferentially stored Hg in roots (7.30 mg/kg) but displayed unexpected Pb mobility (TF=3.81). Zinc accumulation remained within safe limits for both species. The BCF values highlighted A. viridis as an effective Phyto stabilizer for Pb (BCF=3.50) and L. sativa for Zn (BCF=1.24). Statistical analysis (p>0.005) confirmed species-specific responses were significant. These findings suggest A. viridis is suitable for phytoremediation in heavily contaminated sites, while L. sativa may be cultivated with caution in moderately polluted soils, provided Pb levels are monitored. The study advances the practical selection of plants for metal-polluted agroecosystems, balancing ecological restoration and food safety. Recommendations include field trials to validate these screen house observations and molecular studies to elucidate the mechanisms behind L. sativa’s anomalous Pb translocation.